Esquemas de incentivos y carteras de inversión innovadoras - Gino Loyola; Yolanda Portilla (Estudios de Economía, 2010)
– This article characterizes the properties of the compensation scheme of delegated portfolio management that would lead to the selection of high risk-high return portfolios. In particular, it provides conditions under which a non-monotone payment structure emerges as an optimal contract, which rewards extreme results and punishes moderate ones.
Keywords: D86; G11; G20; G30; J33; M52; 330; executive compensation; delegated portfolio management; nonmonotone incentive schemes; non-monotone likelihood ratio property